Ancient Egypt - Shuter, Jane (England Wayland Publishers, 1999)
Highlights the many archaeological digs and findings in Egypt and discusses what life was like in ancient Egypt. Suggested level: primary, intermediate.
Including Color Illustration, Glossary and Index
Keywords: Egypt -- Civilization -- Antiquities